LEGAL PROTECTION FOR EMPLOYEES DUE TO NON-PAYMENT OF HEALTH SOCIAL SECURITY CONTRIBUTIONS BY THE COMPANY - Ardan, Lukman Hakim; Prawesthi, Wahyu; Marwiyah, Siti; Amiq, Bachrul (Fakultas Hukum Universitas Padjadjaran, 2024)
National Social Security will be administered by the BPJS, which consists of the Health BPJS and the Employment BPJS. The obligations of companies are to register as BPJS participants and pay BPJS membership dues. This research aims to understand and analyze the legal provisions if the company does not pay BPJS Health contributions even though it has deducted employee salaries. Apart from that, this research also aims to understand and analyze legal protection for employees who are not paid BPJS Health by the company. The type of method applied in this research is normative legal research. Companies are required to register themselves and their workers as Participants in BPJS. The sanction for those who do not register are administrative sanctions and criminal sanctions are imposed if the company is proven to have committed a crime of embezzlement by not paying salary deductions. The dispute resolution mechanism for BPJS Health participants who do not receive health services is mediation or negotiation before taking the litigation route or trial process in court